Kidney protective effects of baroreflex activation therapy in patients with resistant hypertension - Wallbach, Manuel (J Clin Hypertens (Greenwich), 2018)
Baroreflex activation therapy (BAT) is approved for the treatment of resistant hypertension. In addition to blood pressure (BP) reduction, pilot studies suggested several organoprotective effects of BAT. Thirty‐two patients with resistant hypertension were prospectively treated with BAT. Besides office BP and 24‐hour ambulatory BP (ABP) measurements, detection of a urinary proteome‐based classifier (CKD273), which has been shown to predict chronic kidney disease (CKD) progression, was carried out at baseline and after 6 months of BAT. Office BP significantly decreased from 170 ± 25/90 ± 18 to 149 ± 29/82 ± 18 mm Hg. Analysis of CKD273 score and eGFR with CKD‐EPI equation at baseline revealed strong correlation (r = 0.568, P < 0.001). After 6 months of BAT, there was no significant change in CKD273 score (−0.061 [95% CI: −0.262 to 0.140], P = 0.601). However, by stratification of the data regarding ABP response, there was a statistically significant (P = 0.0113) reduction in the CKD273 score from a mean of 0.161 [95% CI: −0.093 to 0.414] to −0.346 [95% CI: −0.632 to −0.060] after BAT in patients with systolic ABP decrease of ≥5 mm Hg. These data emphasized potential nephroprotective effects of BAT in patients with sufficient BP response.